(untitled) (PERENNIAL, 2018)
One of the many problems of pine wood as furniture raw material is bluestain attack. The purpose of this research was to improve the quality appearance of pine wood by using oil and heat treatments. Materials used in this study consist of four attack levels of pine wood, namely heavy, moderate, mild and no attack. Oil heat treatment condition was 200ºC for 1 and 2 hours, while heat treatment condition was 170ºC, 185ºC and 200ºC for 1 and 2 hours. Eight treatments had been applied for this research with three replicas. The result of this study indicates that pine wood for any treatment using oil heat treatment is darker compared to control, so the bluestain is less apparent. Meanwhile, heat treatment has no effect to improve the quality appearance. Key words: Pinus merkusii, bluestain, quality enhancement, oil heat treatment, heat treatment